2012
DOI: 10.1099/mic.0.053983-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis thymidylate synthase gene thyX is essential and potentially bifunctional, while thyA deletion confers resistance to p-aminosalicylic acid

Abstract: Thymidylate synthase (TS) enzymes catalyse the biosynthesis of deoxythymidine monophosphate (dTMP or thymidylate), and so are important for DNA replication and repair. Two different types of TS proteins have been described (ThyA and ThyX), which have different enzymic mechanisms and unrelated structures. Mycobacteria are unusual as they encode both thyA and thyX, and the biological significance of this is not yet understood. Mycobacterium tuberculosis ThyX is thought to be essential and a potential drug target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
74
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 41 publications
3
74
0
2
Order By: Relevance
“…Consistent with this model for the PAS mode of action, overexpression of an alternate enzyme with dihydrofolate reductase activity, RibD, confers resistance to this drug (8). Interestingly, loss-of-function mutations in thyA, which encodes a folate-dependent thymidylate synthase, have been associated with PAS resistance by an undefined mechanism in both laboratory and clinical isolates of M. tuberculosis (9,10). As only one-third of PAS-resistant clinical isolates have been found to harbor thyA mutations, and not all thyA mutations are associated with PAS resistance (10)(11)(12), additional PAS resistance alleles have yet to be identified.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Consistent with this model for the PAS mode of action, overexpression of an alternate enzyme with dihydrofolate reductase activity, RibD, confers resistance to this drug (8). Interestingly, loss-of-function mutations in thyA, which encodes a folate-dependent thymidylate synthase, have been associated with PAS resistance by an undefined mechanism in both laboratory and clinical isolates of M. tuberculosis (9,10). As only one-third of PAS-resistant clinical isolates have been found to harbor thyA mutations, and not all thyA mutations are associated with PAS resistance (10)(11)(12), additional PAS resistance alleles have yet to be identified.…”
mentioning
confidence: 73%
“…Interestingly, loss-of-function mutations in thyA, which encodes a folate-dependent thymidylate synthase, have been associated with PAS resistance by an undefined mechanism in both laboratory and clinical isolates of M. tuberculosis (9,10). As only one-third of PAS-resistant clinical isolates have been found to harbor thyA mutations, and not all thyA mutations are associated with PAS resistance (10)(11)(12), additional PAS resistance alleles have yet to be identified. Very recently, Zheng et al (8) described a spontaneous PAS-resistant isolate of M. tuberculosis H37Rv harboring a substitution mutation in folC that was responsible for PAS resistance, suggesting that PAS resistance can also be mediated by alterations in dihydrofolate synthase.…”
mentioning
confidence: 99%
“…In addition, mutations causing an overexpression of RibD, which can act as an alternative dihydrofolate reductase (DHFR/DfrA), confer resistance (5, 6). Finally, loss-of-function mutations in thymidylate synthase ThyA, which is a major consumer of tetrahydrofolate, result in PAS resistance (7,8).Other studies reported that one-third of PAS-resistant isolates had thyA mutations; however, little is known about the antibiotic resistance mechanism(s) in the remaining samples (9, 10). Here, we first randomly selected PAS-resistant isolates to determine their genotypes for folC, thyA, and ribD.…”
mentioning
confidence: 92%
“…Phylogenetic polymorphisms exist within antibiotic resistance genes, which might lead to false associations made between certain polymorphisms and phenotypic resistance (23,24). For example, in our study, isolates carried the mutation T202A in thyA, a marker for the LAM lineage of M. tuberculosis that is not responsible for PAS resistance (8,25). Theoretically, these false associations would be identified by detecting the occurrence of mutations in both susceptible and resistant strains from within the same genotype (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation